Pengaruh Keterlibatan Kerja, Work-Life Balance, dan Kepuasan Kerja terhadap Kesejahteraan Karyawan PT. Primatexco Indonesia - Muhammad Izzul Haq; Mohammad Fauzan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to explain the influence of work engagement, work-life balance, and job satisfaction on employee welfare at PT Primatexco Indonesia. This research is a type of explanatory research. The number of samples in this study is 100 employees of the operator section (Weaving). Data collection uses the distribution of questionnaires in the form of Google Forms to all respondents. The tests used in this study are instrument tests, model feasibility tests, and hypothesis tests and data processing using SPSS. The findings of the study (1) Work involvement has a positive effect on employee welfare (2) Work Life Balance has no positive effect on employee welfare (3 Job satisfaction has a positive effect on employee welfare